Pan-genome analysis of Streptococcus suis serotype 2 highlights genes associated with virulence and antibiotic resistance - Zhou, You; Tu, Teng; Yao, Xueping; Luo, Yan; Yang, Zexiao; Ren, Meishen; Zhang, Ge; Yu, Yuanyuan; Lu, Aiping; Wang, Yin (Frontiers in Microbiology, 2024)
Streptococcus suis serotype 2 (SS2) is a Gram-positive bacterium. It is a common and significant pathogen in pigs and a common cause of zoonotic meningitis in humans. It can lead to sepsis, endocarditis, arthritis, and pneumonia. If not diagnosed and treated promptly, it has a high mortality rate. The pan-genome of SS2 is open, and with an increasing number of genes, the core genome and accessory genome may exhibit more pronounced differences. Due to the diversity of SS2, the genes related to its virulence and resistance are still unclear. In this study, a strain of SS2 was isolated from a pig farm in Sichuan Province, China, and subjected to whole-genome sequencing and characterization. Subsequently, we conducted a Pan-Genome-Wide Association Study (Pan-GWAS) on 230 strains of SS2. Our analysis indicates that the core genome is composed of 1458 genes related to the basic life processes of the bacterium. The accessory genome, consisting of 4337 genes, is highly variable and a major contributor to the genetic diversity of SS2. Furthermore, we identified important virulence and resistance genes in SS2 through pan-GWAS. The virulence genes of SS2 are mainly associated with bacterial adhesion. In addition, resistance genes in the core genome may confer natural resistance of SS2 to fluoroquinolone and glycopeptide antibiotics.This study lays the foundation for further research on the virulence and resistance of SS2, providing potential new drug and vaccine targets against SS2.